ANALISIS PERAN LEMBAGA PEMASYARAKATAN DALAM PEMBENTUKAN POLA PENDIDIKAN ANAK DI LPKA KLAS 1 PALEMBANG - Muhammad Pithra Anugra (SOSIOEDUKASI, 2022)
in Indonesia a Penitentiary is a place to provide guidance to prisoners and correctional students. Correctional institutions are required to foster and return correctional inmates to the community. The process of coaching prisoners really needs to be done so that the perpetrators of criminal acts do not repeat the mistakes they have made so that they are no longer disturbing the community. This study uses a quantitative approach, with the type of research library research. Data was collected using observation techniques, books, and literature reports on the results of previous studies. Research data in the form of documentation and literature with some literature. Data analysis activities using interactive analysis models, starting from stage (1) data reduction; (2) data presentation; and (3) drawing conclusions. The results showed that the education pattern used in conducting coaching at LPKA Klas 1 Palembang used the correctional system which was implemented since 1964 which was then supported by the issuance of Law Number 12 of 1995 concerning Corrections. Correctional Institutions play a role in restoring the dignity and worth of prisoners in prison so that they can be accepted in the community again. This is done by providing a coaching program which includes personality development and independence development. The guidance given to prisoners includes four stages, in which the stages are carried out sequentially which include (1) the admission and orientation stage or the introduction stage, (2) the Coaching Stage, (3) Assimilation Phase, (4) Integration Phase.